Soil Arthropods Diversity in Sungai Suci Bengkulu Ecosystem - Fauzi, Ariffatchur; Zarkani, Agustin; Putra, Apriza Hongko; Ifebri, Rihan; Wibowo, Hariz Eko; Putri, Elsa Lolita; Nadrawati, Nadrawati (AGRITROPICA : Journal of Agricultural Sciences, 2024)
Sungai Suci is a part of Bengkulu that is 400 meters above sea level. Sungai Suci is located in a coral coastal area with three ecosystems: the bamboo ecosystem and the sea pine ecosystem; soil arthropods are among the animals that inhabit those two environments. This study aims to look into the variety of soil arthropods in the ecosystem of Sungai Suci. Sampling bamboo and sea pine ecosystems was done by taking soil from the root areas of bamboo and sea pine. For each ecosystem, five soil samples are taken randomly as replication. The soil was placed in a smaller funnel and left for two weeks at room temperature 24ºC, and 12 hours of irradiation. Soil arthropods obtained from the three ecosystems were identified, and their numbers were recorded. The most common type of arthropod found in the three ecosystems was acarina. The study results showed that the diversity values of the bamboo and sea pine ecosystems, respectively, were 1.44 and 0.49; and. Dominance values for the bamboo and sea pine ecosystems, respectively, are 0.38 and 0.82. The evenness values of the bamboo and sea pine, respectively, are 0.56 and 0.18.